2013
DOI: 10.1111/add.12315
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine implants for treatment of opioid dependence: randomized comparison to placebo and sublingual buprenorphine/naloxone

Abstract: Aims To evaluate safety and efficacy of buprenorphine implants (BI) versus placebo implants (PI) for the treatment of opioid dependence. A secondary aim compared BI to open-label sublingual buprenorphine/naloxone tablets (BNX). Design Randomized, double-blind, placebo-controlled trial. Subjects received either 4 buprenorphine implants (80 mg/implant) (n=114), 4 placebo implants (n=54), or open-label BNX (12–16 mg/d) (n=119). Setting 20 addiction treatment centers. Participants Adult outpatients (ages 18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(95 citation statements)
references
References 17 publications
4
91
0
Order By: Relevance
“…In light of our early analysis here, we predict that successful retention will be associated with BMT education during residency, relaxed BMT program rules, and methods that reduce diversion without preventing treatment, e.g. buprenorphine implants (Ling et al, 2010; Rosenthal et al, 2013). …”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In light of our early analysis here, we predict that successful retention will be associated with BMT education during residency, relaxed BMT program rules, and methods that reduce diversion without preventing treatment, e.g. buprenorphine implants (Ling et al, 2010; Rosenthal et al, 2013). …”
Section: Discussionmentioning
confidence: 94%
“…Five studies were excluded on the basis that they did not include a follow-up period of 1 month or longer. One study was excluded on the basis that it did not maintain patients for at least 14 days before taper (Rosenthal et al, 2013). Five studies of buprenorphine outcomes met all criteria (Breen et al, 2003; Ling et al, 2009; Sigmon et al, 2013; Weiss et al, 2011; Woody et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Buprenorphine release is dependent on the rate of dissolution and passive diffusion through the EVA copolymer matrix . Probuphine pharmacokinetics are consistent across all human clinical trials . Maximal plasma concentrations are achieved within 24 h of administration and decline exponentially to a low, non‐fluctuating concentration from week 4 to week 24 eliminating typical peaks and troughs associated with SL administration.…”
Section: General Informationmentioning
confidence: 84%
“…The contemporary clinical use of opioid agonists as ADs in clinical practice remains highly limited because of unresolved issues of abuse and dependence. 17 To overcome the limitations of opioid agonists, a combination of a µ and κ opioid partial agonist, buprenorphine, and a mu opioid antagonist samidorphan were developed. The results of a multicenter, randomized, double-blind, placebo-controlled study have shown that the modulation of the opiate system may be a novel treatment approach for treatment-resistant depression.…”
Section: New Drugs Opioidsmentioning
confidence: 99%